Aliovalent substitution in phosphide‐based materials – Crystal structures of Na10AlTaP6 and Na3GaP2 featuring edge‐sharing EP4 tetrahedra (E=Al/Ta and Ga). Issue 18 (12th June 2021) - Restle, Tassilo M. F.; Zeitz, Sabine; Meyer, Jan; Klein, Wilhelm; Raudaschl‐Sieber, Gabriele; Karttunen, Antti J.; Fässler, Thomas F.
Abstract: Recently, ternary lithium phosphides have been studied intensively owing to their high lithium ion conductivities. Much less is known about the corresponding sodium‐containing compounds, and during investigations aiming for sodium phosphidotrielates, two new compounds have been obtained. The sodium phosphidoaluminumtantalate Na10 AlTaP6, at first obtained as a by‐product from the reaction with the container material, crystallizes in the monoclinic space group P 21 / n (no. 14) with lattice parameters of a =8.0790(3) Å, b =7.3489(2) Å, c =13.2054(4) Å, and β =90.773(2)°. The crystal structure contains dimers of edge‐sharing [(Al0.5 Ta0.5 )P4 ] tetrahedra with a mixed Al/Ta site. DFT calculations support the presence of this type of arrangement instead of homonuclear Al2 P6 or Ta2 P6 dimers. The 31 P and 23 Na MAS NMR as well as the Raman spectra confirm the structure model. The assignment of the chemical shifts is confirmed applying the DFT‐PBE method on the basis of the ordered structural model with mixed AlTaP6 dimers. The sodium phosphidogallate Na3 GaP2 crystallizes in the orthorhombic space group Ibam (no. 72) with lattice parameters of a =13.081(3) Å, b =6.728(1) Å, and c =6.211(1) Å and is isotypic to Na3 AlP2 . Na3 GaP2 exhibits linear chains of edge‐sharing 1 ∞ [GaP4/2 ] tetrahedra. For both compounds band structure calculations predict indirect band gaps of 2.9 eV. Abstract :